Toxic and allelopathic ipomoea yields plant-friendly organic fertilizer. (1st April 2017) - Hussain, Naseer; Abbasi, Tasneem; Abbasi, S.A.
Abstract: The composition and the fertilizer value of vermicompost derived solely from ipomoea, a weed known for its toxicity and allelopathy, has been studied employing Fourier transform Infrared Spectroscopy (FT-IR) and plant bioassay (germination and seedling growth). The impact of ipomoea's vermicompost on the physicochemical and biological characteristics of the soil was also studied. FT-IR analysis revealed that chemical compounds that are responsible for the deleterious effect of ipomoea are largely destroyed in the course of ipomoea's vermicomposting. The ipomoea vermicompost was seen to be a good organic fertilizer as it significantly enhanced germination success, promoted growth of the seedlings and induced plant friendly physicochemical and biological features to the soil. The studies raise the possibility that very large quantities of biomass that are generated by ipomoea across the world can be utilized in producing organic fertilizer through vermicomposting. This may also provide a means of checking the seemingly unstoppable spread of ipomoea and cushioning its adverse impacts.